The current distribution of pond slider Trachemys scripta (Reptilia: Emydidae) in Croatia - Toni Koren; Ana Štih; Ivona Burić; Katarina Koller; Boris Lauš; Mladen Zadravec (Natura Sloveniae)
The pond slider Trachemy scripta was one of the most commonly exported turtles until the last decade and often released into the wild outside its native range. It was introduced to Europe, Africa, South America and Asia and included on the EU list of 100 World's Worst Invasive Alien Species and the List of invasive alien species of Union concern. The import of the subspecies Trachemys scripta elegans into Europe and Croatia has been banned for some time, but the number of specimens recorded in nature is still increasing. In this paper we present 45 new localities were the species was observed in Croatia, which makes a total of 84 known localities. Most of the records, 58%, are in the Continental biogeographical region and the rest in the Mediterranean. It has not yet been recorded for the Alpine biogeographical region. Most records (42%) come from ponds. Three new sightings of females digging nests, laying eggs and sightings of hatchlings were recorded, suggesting successful reproduction of the species. Further surveys of this alien species in Croatia are needed.